Implementation of Deep Learning in Independent Curriculum: Literature Study and Implications for Future Education - Arina, Ida; Tri Herlambang, Yusuf (Jayapangus Press, 2025)
In today's digital era, various significant new challenges and opportunities are faced by the world of education. The Independent Curriculum implemented in Indonesia is designed to provide freedom and comfort to students in developing their potential. In this context, the application of the Deep Learning concept is considered increasingly important. This study aims to discuss the application of Deep Learning in the Independent Curriculum and its application to future education. The literature study method with a qualitative descriptive approach is used to describe and analyze the application of Deep Learning in the Independent Curriculum. The main focus of the study is the collection and analysis of information from relevant literature sources. Based on the literature study that has been conducted, a significant impact on future education can be provided by the application of Deep Learning in the Independent Curriculum. Some important aspects include personalization of learning, data analysis, interactive content, improving the quality of teaching, the potential of artificial intelligence (AI), and preparation for the future.